2013
DOI: 10.1186/1471-2369-14-142
|View full text |Cite
|
Sign up to set email alerts
|

Placental growth factor may predict increased left ventricular mass index in patients with mild to moderate chronic kidney disease – a prospective observational study

Abstract: BackgroundPlacental growth factor [PlGF) is a cardiovascular (CV) risk marker, which is related to left ventricle hypertrophy (LVH) in animal models. Currently there are no data available regarding the possible relationship of PlGF and the development of LVH or diastolic dysfunction in patients with chronic kidney disease (CKD) and the relationship of PlGF to other CV risk factors in CKD patients. The aim of our study was to determine the possible association of PlGF and several other CV risk markers to echoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
2
13
1
Order By: Relevance
“…Of note, echocardiographic findings were similar in the high and low PlGF groups. One clinical study has shown that PlGF is strongly associated with elevated LVMI in patients with stage 2-4 CKD [26], whereas we found no significant relationship between PlGF and LVMI in dialysis patients. Additionally, patients with above-median PlGF levels had similar left ventricular systolic and diastolic function as those with below-median PlGF levels.…”
Section: Discussioncontrasting
confidence: 56%
“…Of note, echocardiographic findings were similar in the high and low PlGF groups. One clinical study has shown that PlGF is strongly associated with elevated LVMI in patients with stage 2-4 CKD [26], whereas we found no significant relationship between PlGF and LVMI in dialysis patients. Additionally, patients with above-median PlGF levels had similar left ventricular systolic and diastolic function as those with below-median PlGF levels.…”
Section: Discussioncontrasting
confidence: 56%
“…As the levels were similar in HF patients with dilated and ischemic cardiomyopathies, the increase of sFlt-1 is not only related to ischemic conditions or coronary artery diseases and several factors could be considered. A role of vascular endothelial growth factor, which can trigger sFlt-1, in angiotensin II-induced vascular inflammation and remodeling, was also suggested [21]. Despite a lack of significant correlation with aldosterone in T2DM patients, we observed a significant relation between sFlt-1 and Gal-3, a known mediator of the fibrotic effect of aldosterone [22].…”
Section: Discussionsupporting
confidence: 47%
“…The use of PlGF alone and BNP alone had similar diagnostic accuracy for prediction of cardiovascular events, and the combination use of PlGF and BNP had higher diagnostic accuracy than either biomarker alone. A recent study has shown that PlGF is a strong predictor of an elevated left ventricular mass index in patents with CKD, 36 suggesting that PlGF may be involved in the development of cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%